Proses Penyelenggaraan Brand Activation Perusahaan Farmasi (Fahrenheit) dalam Upaya Re-Branding Produk - Muhammad Kasthe Firdaus; Rimsky K. Judiseno (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2020)
Corporate Events are activities that are fully funded by companies that have specific objectives to promote their products, create good image for consumers, or give awards to internal parties. For example in research conducted by the author about brand activation activities carried out by pharmaceutical companies to promote their products. Carrying out the activation activities is not only to promote the product, but the company will not increase public recognition of the product. If the requested activity goes well and the services provided by the company to consumers, convey a good impression, of course this will give positive results for the company. Today many private companies are struggling to inject large-scale funds just to improve their good image, public awareness, and appreciation of the products they produce. Because people today are very addictive with the use of gadgets, the thing that companies do is to support their products through social media, which of course costs more than print or physical media. Thus, activating the brand is done in a unique way so that it can attract the interest of the community to take these activities. In this study, the authors used the Observation and Documentation Analysis Method. The results of this study will be given to the campus as an assignment to fulfill the seventh semester graduation requirements at the Jakarta State Polytechnic, Commerce Administration Department, MICE Study Program.